Experiential learning to foster transformational leadership in students from the highlands of Peru - Martínez, Elba Aurora Villar; Vera, Juan Raúl Egoavil (Edelweiss Applied Science and Technology, 2024)
The importance of transformational leadership assumes a very significant role in the educational field, especially in basic education, highlighting the enhancement of experiential learning and the comprehensive development of students. This research aimed to establish the relationship between experiential learning and transformational leadership among students in a rural com-munity in the Peruvian highlands. The study was conducted with a sample of 253 teachers from the central highland region. The research design was quantitative, non-experimental, cross-sectional, and correlational in nature. Questionnaires were used to collect data, which were ana-lyzed using the Spearman Rho test, yielding a correlation coefficient of r=0.512 with a signifi-cance level of 0.002. These results allowed for the rejection of the null hypothesis and confirmed the hypothesis that transformational leadership has a significant impact on students' experiential learning. The instruments used to measure the variables showed high reliability, with Cronbach's alpha coefficients of 0.863 and 0.847 for transformational leadership and experiential learning, respectively. It was concluded that effective transformational leadership can signifi-cantly contribute to the academic and personal development of students, creating an enriching and stimulating educational environment, especially in remote areas with limited access to reg-ular education.